(untitled) (Research, Society and Development, 2020)
Objective: To draw an epidemiological profile of neglected diseases of compulsory notification in Brazil, and to analyze government investments in this area. Methodology: This is a descriptive and retrospective study, conducted between 2007 and 2017, with the universe of reported data on neglected diseases in Brazil, including dengue, visceral leishmaniasis, malaria, schistosomiasis, Chagas disease, tuberculosis and leprosy. Results: It was observed that the disease with the largest number of reported cases in the period was leprosy with a higher predominance in males, cases such as malaria, tuberculosis and visceral leishmaniasis in which there is a significant difference between genders. Regarding the number of deaths, it was found that there was a highlight for Tuberculosis, however, in some cases, the patient’s death was due to other causes, such as existing comorbidities or complications thereof. Conclusion: In Brazil, some of these diseases receive greater attention from the government, significantly reducing the number of cases, such as leprosy, schistosomiasis and dengue. But other diseases, such as tuberculosis, which have already been targeted by government campaigns, do not have much investment today and the number of cases has changed little over the past 10 years.